An introduction to using blockchain for internet of things security. (30th September 2021) - Ahuja, Sanjay P.; Wheeler, Nathan
The internet of things (IoT) is an emerging paradigm with the potential to disrupt entire industries. Machine-to-machine communication and automated action taken in the physical world present opportunities for automation that have never been possible before. However, being still in its infancy, IoT still has many outstanding opportunities for improvement, one of which being security. Blockchain, along with some supporting technologies such as cryptography, enables a decentralised, highly secure and immutable database of transactions. The benefits promised by blockchain would complement the current IoT ecosystem tremendously. In this paper, we delve into the details of blockchain from Nakamoto's original paper on bitcoin and explore opportunities to leverage this technology to empower IoT security. We explore blockchain's applicability as a platform for IoT security in the realm of smart homes, smart cities and in a new decentralised IoT public key infrastructure.